2008
DOI: 10.1111/j.1462-2920.2008.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial ectosymbionts and virulence silencing in a Fusarium oxysporum strain

Abstract: In the present article we have ascertained the presence of a consortium of ectosymbiotic bacteria belonging to Serratia, Achromobacter, Bacillus and Stenotrophomonas genera associated to the mycelium of the antagonistic Fusarium oxysporum MSA 35 [wild-type (WT) strain]. Morphological characterization carried out on the WT strain, on the F. oxysporum MSA 35 without ectosymbionts [cured (CU) strain] and on the pathogenic F. oxysporum f.sp. lactucae (Fuslat 10) showed that the ectosymbionts, present only in the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 59 publications
4
73
0
2
Order By: Relevance
“…Our in vitro study revealed that RDA01, NICS01, and DFC01 inhibit Fusarium fungal growth by 49% in PDA medium (Figure 9a). The antagonistic fungi produced volatile secondary metabolites inhibit the growth of Fusarium and protect the plant disease against pathogens (Minerdi et al 2008(Minerdi et al , 2009(Minerdi et al , 2011. The results of the pot experiment under greenhouse conditions confirmed the biocontrol ability of NICS01 and DFC01 against Fusarium, as evidenced by increases in plant growth (Figure 9b).…”
Section: Effect Of Fungal Treatments On the Primary And Secondary Metsupporting
confidence: 55%
“…Our in vitro study revealed that RDA01, NICS01, and DFC01 inhibit Fusarium fungal growth by 49% in PDA medium (Figure 9a). The antagonistic fungi produced volatile secondary metabolites inhibit the growth of Fusarium and protect the plant disease against pathogens (Minerdi et al 2008(Minerdi et al , 2009(Minerdi et al , 2011. The results of the pot experiment under greenhouse conditions confirmed the biocontrol ability of NICS01 and DFC01 against Fusarium, as evidenced by increases in plant growth (Figure 9b).…”
Section: Effect Of Fungal Treatments On the Primary And Secondary Metsupporting
confidence: 55%
“…It is known that chlamydospores with thick walls are developed by the modification of hyphal and conidial cells under unfavorable environmental conditions, such as at low temperature, and these resting bodies act as primary inocula in subsequent soil-borne infections, whereas the microconidia and macroconidia formed by F. oxysporum are important in secondary infection [35] [36]. Minerdi et al [37] reported that microbial symbionts silence the virulence of F. oxysporum and that changes in cell morphogenesis by F. oxysporum underlie this suppression.…”
Section: Discussionmentioning
confidence: 99%
“…For Fusarium oxysporum, hyphae-associated bacteria were shown to produce the volatile sesquiterpene caryophyllene, which repressed the expression of two virulence genes. When cured from the bacterial symbionts, caryophyllene was not detected and F. oxysporum became pathogenic (Minerdi et al, 2008).…”
Section: Volatile-mediated Antifungal Activitymentioning
confidence: 99%
“…Furthermore, exposure to bacterial volatiles has been reported to change fungal morphology, enzyme activity and gene expression (Wheatley, 2002;Vespermann et al, 2007;Minerdi et al, 2008Minerdi et al, , 2009Kai et al, 2009;Garbeva et al, 2011Garbeva et al, , 2014b. For example, activity of laccases and tyrosinases can be strongly affected by bacterial volatiles (Wheatley, 2002).…”
Section: Volatile-mediated Antifungal Activitymentioning
confidence: 99%